Tim Berners-Lee - Jason Porterfield
People use the World Wide Web for everything from paying bills and buying products and services to turning in work or school assignments and helping people stay in touch. This is the story of Tim Berners-Lee, the inventor of the Web, from his birth in London, England, to his physics studies at Queens College, Oxford, and his work as a software engineer at CERN in Geneva. He created the Web, specifications for URLs, HTTP, and HTML, and the first web browser. He also founded the World Wide Web Consortium (W3C) at MIT in 1994 to develop international Web standards.